Peranan Alat Bukti Elektronik dalam Tindak Pidana Pencemaran Nama Baik - I Putu Angga Permana; I Made Arjaya; Ni Made Sukaryati Karma (Jurnal Interpretasi Hukum, 2021)
This study is included in the category of empirical legal research carried out to fulfill the following objectives, 1) Assessing the rules related to criminal act of defamation in the Information and Electronic Transactions Law, 2) Examining the process of legal proof in criminal act of defamation under the Law of Information and Electronic Transactions. From the results of data analysis, it can be concluded that along with the increasing number of criminal cases through online media, the enforcement of electronic documents as legal evidence becomes very important due to the absence of physical evidence. The rules regarding the criminal act of defamation are included in the "Law. No.11 / 2008 article 5 paragraph (1) and (2) on Information and Electronic Transactions "where the presence of this new law is an enlightenment related to online criminal cases (cybercrime). Then, it was also found that only if the use of trial evidence was in accordance with the existing regulations in Indonesia, then proof of a criminal act, especially defamation, could be said to be legitimate. Substantially, defamation is classified as a criminal offense, so it is necessary to have a way of proof if the case occurred is not physically but through online media (Cybercrime).